L’historicisation de l’homosexualité dans La volonté de savoir : une des voies d’appropriation de Foucault par les études de genre - Julie Mazaleigue-Labaste (Genre, Sexualité et Société)
Foucault is now an major reference for gender studies and feminist studies. This raises a paradox at first sight: he never explicitly used gender as a category in his work, and he made few, if any, references to feminist studies that were contemporary to him. In this paper, we will point out one of the ways Foucault has become a central reference for gender studies: the reception in the early gay and lesbian studies (before the queer turn) of the project of historicization of sexual identity in The Will to Knowledge. In the political and academic context of sexual liberation and gay and lesbian activism in North America in the 1970s and early 1980s, the reception of The Willing to Knowledge led gay and lesbian studies to focus on a particular moment in the text: the anti-essentialist history of homosexuality, homosexuality being conceived as a historical and political production that articulates gender identity, sexual orientation, and normalization.